Hubungan Persepsi Terhadap Integriti Ketua, Etika Kepimpinan dan Etika Kerja Islam di Kalangan Subordinat - Zain Ali, Abdul Ghani (2010)
The main purpose of the study is to examine the relationship between perception of leader integrity, ethical leadership and Islamic work ethic among subordinate in Jabatan Kehakiman Syariah Negeri Kedah (JKSNK). Most of 84 fiom 100 respondents were selected by using simple random system (SRS) involved in this study. The finding indicates no significant relationship between perception of leader integrity, ethical leadership and Islamic work ethic. Also, multiple regressions indicate that perception of leader integrity and ethical leadership is not influence Islamic work ethic significantly. So, the findings in this study cannot proof the evidences that perception of leader integrity and ethical leadership is influence Islamic work ethic. Furthermore, finding indicates a significant difference of Islamic work ethic among area of residence significantly.